Identification of potential target genes in Homo sapiens, by miRNA of Triticum aestivum: a cross kingdom computational approach - Sánchez Romo, Daniel; Hernández Vásquez, César Ignacio; Pereyra Alférez, Benito; García García, Jorge Hugo (KeAi Communications, 2022)
Plant-derived miRNAs can be found in the human body after dietary intake, and they can affect post-transcriptional gene regulation in human. It is important to identify targets to determine the possible effects in human genes by using computational approach. In this study, 787 possible mRNAs human targets were predicted by 84 miRNAs of wheat. A total of 14 miRNAs were identified with individual binding to 33 mRNAs associated with schizophrenia, epilepsy, neurodevelopmental disorders, and various cancers, located in the 3′UTR of the mRNA. A functional enrichment was carried out, where the results showed associations to pathways such as dopaminergic synapse (hsa04728), and signaling pathways, significantly associated with the target genes. The prediction of target mRNAs in humans by wheat miRNAs, offer candidates that could facilitate the search and verification, which could be of relevance for future projects and there for contribute in the therapeutic treatment of various human diseases.